Interactions between microplastics and contaminants: A review focusing on the effect of aging process - Luo, Hongwei; Tu, Chaolin; He, Dongqin; Zhang, Anping; Sun, Jianqiang; Li, Jun; Xu, Juan; Pan, Xiangliang (The Science of the total environment, 2023)
Microplastics (MPs) in the environment are a major global concern due to their persistent nature and wide distribution. The aging of MPs is influenced by several processes including photodegradation, thermal degradation, biodegradation and mechanical fragmentation, which affect their interaction with contaminants. This comprehensive review aims to summarize the aging process of MPs and the factors that impact their aging, and to discuss the effects of aging on the interaction of MPs with contaminants. A range of characterization methods that can effectively elucidate the mechanistic processes of these interactions are outlined. The rate and extent of MPs aging are influenced by their physicochemical properties and other environmental factors, which ultimately affect the adsorption and aggregation of aged MPs with environmental contaminants. Pollutants such as heavy metals, organic matter and microorganisms have a tendency to accumulate on MPs through adsorption and the interactions between them impact their environmental behavior. Aging enhances the specific surface area and oxygen-containing functional groups of MPs, thereby affecting the mechanism of interaction between MPs and contaminants. To obtain a more comprehensive understanding of how aging affects the interactions, this review also provides an overview of the mechanisms by which MPs interact with contaminants. In the future, there should be further in-depth studies of the potential hazards of aged MPs in different environments e.g., soil, sediment, aquatic environment, and effects of their interaction with environmental pollutants on human health and ecology. [Display omitted] •The aging process of MPs can change their physicochemical properties.•Aging processes affect the interaction of contaminants with MPs.•The interaction mechanisms between contaminants and MPs are elucidated.•Methods to explore the interactions between pollutants and MPs are summarized.